Diagram Kendali MAD pada Harga Cabai Rawit di Jawa Tengah - Norasia, Yolanda (Jurnal Matematika, 2021)
Food price policies affect the stabilization of food prices in Indonesia. The control chart is one of the tools used to measure the stabilization of food prices. The control chart was first introduced by W.A. Shewhart. The Shewhart control chart is divided into two, namely attribute and variable control charts. Shewhart's control chart uses normal distribution assumptions. In the fact, the real data not always follow the normal distribution. Deviations that occur due to large data variability. The MAD control chart is used to observe process variability. The MAD control chart has three horizontal lines, namely the Center Line (CL), Upper Center Line (UCL), and Lower Center Line (LCL). Median Absolute Deviation (MAD) control charts using the median and MAD subgroups. By using the MAD control chart, the increase in chili prices shows that it is not statistically controlled.